OPTIMASI FORMULA MATRIKS TRANSDERMAL PENTAGAMAVUNON-0 DENGAN KOMBINASI POLIMER POLYVINYLPYROLLIDONE DAN POLIVINIL ALKOHOL MENGGUNAKAN SIMPLEX LATTICE DESIGN - , Nirwati Rusli ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PGV-0 delivery in oral route is difficult due to the high intensity of first-pass metabolism. Delivery of PGV-0 in transdermal matrix formulation can be attractive. This research aimed to determine effect of combination PVP and PVA polymers on the was physicochemical properties and the release rate of PGV-0 matrix, and the in vitro transdermal transport profile of the optimum formula across the skin. The design of matrix formulation was based on simplex lattice design by using Design Expert software version 7.1.5. Physicochemical properties such as visual observasion, weight, thickness, moisture content, moisture uptake, folding endurance, drug content of the matrix, and release rate of PGV-0 from the matrix was evaluated. The cumulative amount of drug released from optimum formula release study were analyzed by using WinSAAM software. In vitro transdermal transport study of PGV-0 through rat skin membrane was performed using vertical diffusion cell. The results provided an information that a combination PVP and PVA polymers had a positive influence on physicochemical properties of the matrix with the moisture uptake between 0.56 to 4.02%, the drug content of 100,51 to 107.58%, and the percent amount of PGV-0 released ranged from 6.13 to 10.87%. The results of the amount of drug released from optimum formula with ratio composition of PVP and PVA (5,5:3) showed that release of PGV-0 from transdermal matrix described by a three-compartment models with first-order kinetic. The in vitro transport of PGV-0 indicated that optimum formula has not been able to deliver sufficient drugs across the skin.